A comparison of acute affective responses, physiological measures and training volume between superset and traditional resistance training in untrained adults - Myraunet, Per Aslak; Saeterbakken, Atle Hole; Andersen, Vidar (Frontiers in Sports and Active Living, 2025)
The aim of this study was to compare the perceptive responses, physiological measures, training volume and training duration comparing a superset vs. a traditional resistance training session in untrained adults. Thirty adults (29 ± 7 years, 1.72 ± 0.1 m, 77 ± 16 kg) performed one superset resistance training session and one traditional resistance training session in a randomized-crossover design. Both sessions consisted of eight exercises with two sets and a load of ∼10-repetition maximum. The outcomes included number of repetitions, training duration, blood lactate and heart rate in addition to rate of perceived exertion (RPE), rate of perceived discomfort (RPD), session displeasure/pleasure (sPDF) and exercise enjoyment (EES) which were recorded in the middle and post-exercise. Forty-eight hours after the last session the participants reported which session they would prefer as their regular routine if they had to choose. The main findings were that the superset session led to greater RPE compared to the traditional session (p = 0.012–0.16, d = 0.53–0.54). Further, there was a trend towards greater RPD after the superset session, although not reaching statistical significance (p = 0.092, d = 0.41). There were no differences for sPDF (p = 0.404) or EES (p = 0.829). Furthermore, the superset session demonstrated higher levels of blood lactate levels (18.3%. p < 0.001, d = 0.81) and average heart rate (7.8%, p < 0.001, d = 1.53) compared to the traditional session. The traditional session took 60% longer time (p < 0.001, d = 6.62), and had 4.6% more repetitions (p = 0.006, d = 0.54) compared to the superset session. Two out of three participants reported the superset session as their preferred regular training routine. In conclusion, the superset session led to a higher perceived effort and discomfort, higher metabolic stress, took less time, had a lower training volume and was more preferred compared to the traditional session in untrained adults.